Emergence of Invasive Serotype Ib Sequence Type 10 Group B Streptococcus Disease in Chinese Infants Is Driven by a Tetracycline-Sensitive Clone - Zhang, Li; Kang, Wen-Juan; Zhu, Lei; Xu, Li-Jun; Guo, Chao; Zhang, Xin-Hua; Liu, Qing-Hua; Ma, Lan (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction: Group B streptococcus (GBS) is a leading cause of serious infection in infants, the extensive use of tetracycline specifically selected GBS clones infecting humans. Sequence type (ST) 10 GBS infant invasive infection is becoming prevalence in China. Our study aims to understand clinical and microbiological characteristics of this GBS strain. Methods: A retrospective study was conducted to collect data from infants with invasive GBS disease in the largest women and children’s medical center in Shanxi between January 2017 and October 2020. GBS isolates were analyzed by capsule serotyping, genotyping, antibiotic resistance and surface protein genes. Results: All the ST10 isolates belonged to serotype Ib, type Ib /ST10 strains were responsible for 66.7% (14/21, P ＜0.05) of infant invasive GBS infections during the period, and all resulted in late-onset (LOD) and late LOD disease (14/14). Infants with type Ib/ST10 GBS diseases had a significantly higher rates of meningitis (9/14, 64.3%, p < 0.05) and clinical complications (5/14, 35.7%, p < 0.05). The Ib /ST10 GBS isolates had limited genetic diversity, clustered in the CC10/bca/PI-1+PI-2a genetic lineage, showed resistance to erythromycin, lincomycin and fluoroquinolones but sensitivity to tetracycline, and possessed genes ermT, ermB as well as having amino acid changes of gyrA and parC. Conclusion: Considering the probable clonal expansion which has the ability to create severe infections in infants and the emerging multi-drug resistant isolates, continued monitoring for type Ib/ST10 GBS infections is warranted. Keywords: Group B streptococcus (GBS), Infants, late-onset disease (LOD), Tetracycline, Meningitis